Pan-Genome Plasticity and Virulence Factors: A Natural Treasure Trove for Acinetobacter baumannii - Theodoros Karampatakis; Katerina Tsergouli; Payam Behzadi (MDPI AG, 2024)
Acinetobacter baumannii is a Gram-negative pathogen responsible for a variety of community- and hospital-acquired infections. It is recognized as a life-threatening pathogen among hospitalized individuals and, in particular, immunocompromised patients in many countries. A. baumannii, as a member of the ESKAPE group, encompasses high genomic plasticity and simultaneously is predisposed to receive and exchange the mobile genetic elements (MGEs) through horizontal genetic transfer (HGT). Indeed, A. baumannii is a treasure trove that contains a high number of virulence factors. In accordance with these unique pathogenic characteristics of A. baumannii, the authors aim to discuss the natural treasure trove of pan-genome and virulence factors pertaining to this bacterial monster and try to highlight the reasons why this bacterium is a great concern in the global public health system.